Applying a new hybrid model of embedded system development methodology on a flood detection system - Suliman, Azizah; Nazri, Nursyazana; Nazeri, Surizal (2017)
The embedded system development methodology has not been as well established as the development methodology in software engineering. Involving inter-disciplinary activities in the development of hardware and software need to be further considered when developing an embedded system. This paper presents a new development model for an embedded system by the hybridization of selected development methodologies in software engineering and systems engineering, considering that they are both essential in embedded system. The model is harmonized with embedded system design vital tasks and also non-functional properties following the ISO/IEC 9126 standard.The model is then applied to a flood detection system for verification purposes.With the phases and steps in the new hybrid model for embedded systems development methodology carefully followed, the system was built in a more systematic and structured manner addressing the every needs of an embedded system’s requirements.